ANALISIS PENGENDALIAN PERSEDIAAN BAHAN BAKU TEMBAKAU DENGAN MENGGUNAKAN METODE EOQ (ECONOMICAL ORDER QUANTITY) GUNA MENCAPAI EFISIENSI TOTAL BIAYA PERSEDIAAN BAHAN BAKU PADA PR. GAMBANG SUTRA KUDUS - Alamsyah, Ilham; Prihatini, Apriatni Endang; Wijayanto, Andi (Jurnal Ilmu Administrasi Bisnis, 2014)
Raw material inventory control system to determine and ensure the availability of supplies of raw materials in quantity, quality and timely manner. The problem in this study is the procurement of raw material inventory of tobacco at PR. Gambang Sutra Kudus still have excess. This is related to the frequency of purchase of raw materials and quantity of raw material purchase, so as to result in waste of working capital that is embedded in the supply of raw materials and the cost of raw materials ordering and storage costs of raw materials. The purpose of this research was to determine how the level of efficiency in the procurement of raw material inventory between EOQ method compared to the company policies of the PR. Gambang Sutra Kudus.The type of research is descriptive analytical research. Data analysis begins with a comparative analysis of the quantity of raw materials, total inventory cost of raw materials and the cost of raw materials between company policies of PR. Gambang Sutra Kudus with EOQ method. Based on the research result shows that by using the EOQ method can be more efficient when compared to the company policies of the PR. Gambang Sutra Kudus, quantity and frequency of purchase raw materials are less but still account for safety stock and reorder point, so that the production process is not disrupted. Beside that, the cost of purchase, ordering cost and holding cost are lower, so as to create efficiencies in the total inventory cost. Â PR. Gambang Sutra Kudus in conducting the procurement of raw material inventory should use the EOQ method for the company to obtain a higher level of efficiency, as well as take into account the safety stock and reorder point in order to avoid excess inventory of raw materials.